2011
DOI: 10.1249/mss.0b013e318216ea37
|View full text |Cite
|
Sign up to set email alerts
|

Technical Ability of Force Application as a Determinant Factor of Sprint Performance

Abstract: Force application technique is a determinant factor of field 100-m sprint performance, which is not the case for the amount of total force subjects are able to apply onto the ground. It seems that the orientation of the total force applied onto the supporting ground during sprint acceleration is more important to performance than its amount.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

39
448
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(496 citation statements)
references
References 34 publications
(64 reference statements)
39
448
3
6
Order By: Relevance
“…[8][9][10][11][12] From a kinetic standpoint, literature reports sled towing to lead to a reduction in normalized mean vertical GRF (3.0 ± 1.6N.kg -1 to 1.7 ± 1.16N.kg -1 ), with concomitant increases in net horizontal impulse (0.75 ± 0.28m.s -1 to 0.97 ± 0.17m.s -1 ) and peak propulsive forces (8.8 ± 2.5N.kg -1 to 9.3 ± 0.9N.kg -1 ) when towing sled loads of as little as 30% body mass (BM). 13 As such, a shift in ratio of forces applied into the ground can be noted, with research by Kawamori, Newton & Nosaka 13 reporting a mean shift in ratio of GRF application (vertical to horizontal) of ~11%, thus bringing about a mechanically more efficient force application throughout ground contact 2 . Further to this, a review by Petrakos, Morin, and Egan 7 examining longitudinal training implications indicates how sled towing with "light" loads (< 10% BM) may infact lead to decrements in sprint acceleration performance (-1.5%, ES = 0.50).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[8][9][10][11][12] From a kinetic standpoint, literature reports sled towing to lead to a reduction in normalized mean vertical GRF (3.0 ± 1.6N.kg -1 to 1.7 ± 1.16N.kg -1 ), with concomitant increases in net horizontal impulse (0.75 ± 0.28m.s -1 to 0.97 ± 0.17m.s -1 ) and peak propulsive forces (8.8 ± 2.5N.kg -1 to 9.3 ± 0.9N.kg -1 ) when towing sled loads of as little as 30% body mass (BM). 13 As such, a shift in ratio of forces applied into the ground can be noted, with research by Kawamori, Newton & Nosaka 13 reporting a mean shift in ratio of GRF application (vertical to horizontal) of ~11%, thus bringing about a mechanically more efficient force application throughout ground contact 2 . Further to this, a review by Petrakos, Morin, and Egan 7 examining longitudinal training implications indicates how sled towing with "light" loads (< 10% BM) may infact lead to decrements in sprint acceleration performance (-1.5%, ES = 0.50).…”
Section: Introductionmentioning
confidence: 96%
“…Research has found that increases in sprint acceleration performance are primarily achieved through optimising the resultant ground reaction force (GRF) vector to facilitate a horizontal (propulsive) orientation. 2,3 As such, literature reports propulsive forces within acceleration to be 46% greater than those observed within maximal velocity running. [4][5][6] Fundamentally therefore, a large training consideration should be noted for training modalities which provide overload to the propulsive nature of GRF application within the acceleration phase of sprint running.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown high levels of horizontal force application is related to faster sprinting speeds. [11][12][13][14][15] Contreras and colleagues 16 found that the hip thrust is effective for improving both horizontal jump distance and sprinting performance.…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, se han encontrado mayores fuerzas horizontales que verticales durante la etapa de aceleración (construcción de la velocidad) (Mero, 1988). Recientemente, se ha definido que los atletas más rá-pidos poseen un ratio mayor de fuerza horizontal que los corredores más lentos (Kugler & Janshen, 2010) y que la técnica de aplicación de la fuerza es un factor determinante en el rendimiento de velocidad (Morin, Edouard & Samozino, 2011). Estos resultados implican que la capacidad de producir un mayor ratio de fuerza horizontal que vertical puede ser más importante que la propia producción de fuerza en general (Kugler & Janshen, 2010).…”
Section: Introductionunclassified